Plant organ rather than cover crop species determines residue incorporation into SOC pools - Engedal, Tine; Hansen, Veronika; Rasmussen, Jim; Magid, Jakob; Mueller, Carsten W.; Thomsen, Sune Tjalfe; Sørensen, Helle; Jensen, Lars Stoumann (Soil biology & biochemistry, 2025)
The implementation of cover crops has emerged as a promising approach to improve soil organic carbon (SOC) stocks, with particular emphasis on the perceived higher carbon use efficiency displayed by high-quality residues such as from leguminous plants. In this study, we explored how different cover crop residues, specifically from a legume and a grass cover crop, affects SOC formation and its distribution across various soil carbon pools. Over a 7-month period, we incubated 14C-labeled winter rye and hairy vetch residues in microcosms containing soils of varying soil fertility levels from a long-term field trial. We tracked the fate of carbon into free and occluded particulate organic matter (fPOM, oPOM), mineral-associated organic matter (MAOM), and carbon deposited outside the detritusphere. Despite notable differences in C:N ratio, chemical composition, and turnover rate, similar SOC formation efficiency between vetch and rye within each plant organ (shoots and roots) was observed. Interestingly, the plant organ appeared to exert a greater influence on the fate of cover crop carbon than whether the crop was leguminous or non-leguminous. This phenomenon seemed to be closely related to the lignin content. At medium soil fertility, we found that the largest proportion of cover crop residue C remained as MAOM (20% for shoots, 15–18% for roots), followed by fPOM (5–6% for shoots, 10–12% for roots) and oPOM (2.7–3.0% for shoots, 1.5–1.6% for roots). Notably, fPOM and oPOM exhibited opposite responses to residue quality, indicating functional distinctions between these often-pooled POM pools. Soil fertility exerted minimal influence on overall respiration rate patterns or SOC formation, although it did affect oPOM formation efficiency, likely due to differences in soil aggregation. In conclusion, our findings challenge the assumption regarding the superiority of N rich leguminous cover crop residues for enhancing SOC accrual in C pools believed to have longer persistence. •Formation efficiency of MAOM and oPOM similar for legume and grass cover crop.•Plant organ more important than species in determining the fate of cover crop C.•For similar C:N ratio, lignin could best explain differences in C fractions.•Soil fertility showed little impact on the fate of cover crop C.